The potential of Eucalyptus hybrids in farm forestry in the semi-arid winter rainfall region of South Africa - Lambrechts, Hugo Amos (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.